Studi Fenomena Minat Siswa Memanfaatkan Layanan Bimbingan dan Konseling di SMP - Nanda Putriana; M. Ramli; Fitri Wahyuni; Nanda Putriana; M. Ramli (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: Guidance and counselling play a crucial role in facilitating student development. Interesting phenomena have been observed on one of the Junior High School in the city of Malang: students’ reluctance to attend the Guidance and Counselling room, their fear and anxiety when called to meet the counsellor and their suboptimal utilisation of Guidance and Counselling services. This qualitative study employed a phenomenological approach to describe students’ interests and the counsellors’ attempts towards Guidance and Counselling services. This study comprised students in seventh through ninth grades, counsellors, principals, vice principals for student affairs, and homeroom teachers serving as informants. The study’s findings indicated that (1) numerous students were interested in classical guidance services. On the other hand, counselling, group guidance, instagram ,and Bookshelf were less desirable; (2) Student interest was affected by elements of perception, school personnel, parents, society, and mass media; (3) counselors stimulate interest through the counseling program according to students' conditions, build harmonious relationships, and collaborate with teacher and parents; (4) School personnel, parents, and the government provide encouraging and inhibiting factors to cultivate student interest, which was subsequently reinforced through classical guidance for seventh grade, home visits, parenting seminars, and peer cooperation. Based on these findings, it is hoped that the counselor will assess the management program for the better. Abstrak: Bimbingan dan konseling memiliki posisi penting dalam memfasilitasi perkembangan siswa. Terdapat fenomena menarik pada salah satu SMP di kota Malang: siswa tidak tertarik mengunjungi ruang Bimbingan dan Konseling, ketakutan dan gugup ketika dipanggil untuk bertemu konselor, serta tidak optimal pemanfaatan layanan Bimbingan dan Konseling. Penelitian kualitatif pendekatan fenomenologi ini bertujuan mendeskripsikan minat siswa beserta upaya konselor terhadap layanan Bimbingan dan Konseling. Informan penelitian adalah siswa kelas VII hingga IX, konselor, kepala sekolah, waka bidang kesiswaan, dan wali kelas. Penelitian menghasilkan temuan yaitu, (1) layanan bimbingan klasikal diminati banyak siswa. Sedangkan, konseling, bimbingan kelompok, instagram, dan rak buku kurang diminati; (2) Minat siswa dipengaruhi persepsi, personil sekolah, orang tua, masyarakat, dan media massa; (3) konselor menumbuhkan minat siswa melalui program BK sesuai kondisi siswa, membangun hubungan harmonis, serta kolaborasi dengan guru dan orang tua; (4) unsur pendukung dan penghambat menumbuhkan minat siswa berasal dari personil sekolah, orang tua, dan pemerintah, kemudian ditindaklanjuti melalui bimbingan klasikal untuk kelas tujuh, kunjungan rumah, seminar pengasuhan anak, dan kerjasama teman sejawat. Berdasarkan temuan tesebut diharapkan konselor mengevaluasi manajemen program menjadi lebih baik.